The value relevance of accounting performance measures for quoted family firms: A study in the light of the alignment and entrenchment hypotheses - Sami Basly; Tayeb Saadi (European Journal of Family Business (EJFB), 2020)
Family business literature shows that family and nonfamily firms differ with respect to their financial reporting decisions. However, although the literature on financial reporting in fami - ly firms has developed over the last ten years, it is mostly oriented towards earnings management and management control issues. Given the specific characteristics of family firms in financing and governance, do their published accounting data have less value relevance for public investors than in the case of non-family firms? How do family firms differ from one another on this issue? While different theoretical perspectives have been used to tackle this problem, two main theses based on agency theory were the most frequently called upon. In fact, the views of interests' alignment and entrenchment are competing in explaining the differential quality of family and non-family firms accounting numbers. This paper draws on this theoretical lens and contributes to filling this research gap by conducting a comparative analysis of earnings' value relevance for a sample of quoted French family and non-family firms. First, it examines whether family firms show more or less relevant accounting earnings than non-family firms. Second, it seeks to study the heterogeneity of family firms in terms of earnings figures' relevance by considering the extent of family control and the involvement of a family CEO as mechanisms leading to alignment or entrenchment. The findings show that family firms exhibit better earnings' value relevance than non-family firms. In addition, when owning families' control becomes high, earnings' value rel - evance worsens, which suggests a possible entrenchment effect on behalf of controlling families.
Keywords: M10; M41; M48; 650; Family firms; Accounting earnings; Value relevance; Agency theory; Alignment hypothesis; Entrenchment hypothesis